Implementation of Local Function Value Nggahi Rawi Pahu in Public Junior School 3 Sanggar Bima, Nusa Tenggara Barat District - Misdiatun, Misdiatun; Suyahmo, Suyahmo; Pramono, Suwito Eko (JESS (Journal of Educational Social Studies), 2019)
Nggahi rawi pahu (speech according to action) is the value of local wisdom, which is the life guide of the Bima community, which must be kept consistent. As the development of the era of consistency began to be eroded by the influence of the development of information technology that brought new values. The purpose of this study was to analyze the implementation of the value of local wisdom from nggahi rawi pahu in Public Junior School 3 Sanggar, Bima West Nusa Tenggara. The research method used qualitatively. Informants in this study were teachers, students, guardians of students, and community leaders. The technique of collecting data was by observation, in-depth interviews, and documentation. The validity of the data in this study used the method of triangulation. The results showed that the Public Junior School 3 Sanggar, Bima District of West Nusa Tenggara was and would continue to strive to implement the value of local wisdom through the nggahi rawi pahu (speech according to deeds) which was adjusted to the subject matter, in an effort to provide: (1) exemplary from the teacher by giving positive examples; (2) instill social values ​​that live in the community; (3) carrying out inhibiting actions, such as giving advice; (4) giving penalties for violating the rules of conduct in an oral and written manner. Business value planting will continue to be carried out with limited facilities and infrastructure. Therefore the cooperation of the social environment is expected to help inherit the value of local wisdom as the identity of the region.